Israelian Hebrew, Inscriptions from the North of Israel, and Samaritan Hebrew: A Complex of Northern Dialects - Rendsburg, Gary A. (Journal for semitics, 2021)
This article surveys the three sources at our disposal for the recovery of ancient northern Hebrew: a) Israelian Hebrew, that is, the dialect present in those portions of the Bible with a northern provenance; b) inscriptions from the northern kingdom of Israel, including Kuntillet ‘Ajrud; and c) Samaritan Hebrew. The overall goal is to determine the common lexical and grammatical features of this complex of northern Hebrew dialects from the biblical period, many of which are shared with Phoenician and Aramaic, though not with Judahite Hebrew.